Non-Invasive Therapeutic Approaches for Mechanical Low Back Pain: An Integrative Systematic Review : Non-Invasive Therapeutic Approaches for Mechanical Low Back Pain - Silva, Guilherme Quireza; N. B. R. Alves, Fernanda; R. Afonso, João Pedro; M. P. Soares, Juliana; A. Souza, Shayra Kellen; M. Rodrigues-Silva, Bruna; P. Mundim Neto, Joaquim; S. I. Tabata, Keyci; R. Alves, Larissa; V. Braga, Lenita; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Mechanical low back pain (LBP) is one of the most prevalent musculoskeletal conditions, affecting a significant portion of the global population at some point in their lives. It is characterized by pain in the lumbar region without an obvious inflammatory or infectious origin, typically exacerbated by movement, posture, or mechanical load. LBP, whether acute, subacute, or chronic, is a leading cause of temporary and permanent disability, with significant economic repercussions due to lost workdays and healthcare costs. Recent clinical guidelines, such as those from the American College of Physicians (ACP) and the National Institute for Health and Care Excellence (NICE), emphasize the importance of non-invasive interventions for managing mechanical LBP, particularly in acute and chronic cases. In this context, this systematic review aims to consolidate current evidence on available therapeutic interventions, focusing on non-invasive treatments. Objective: To evaluate the available evidence on non-invasive therapeutic interventions for the treatment of mechanical low back pain. The review aims to synthesize international clinical guideline recommendations and identify the most effective practices for reducing pain and improving functional outcomes. Methods: This review was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Randomized controlled trials, systematic reviews, and clinical guidelines published up to 2023 addressing the management of mechanical low back pain in adults were included. Databases such as PubMed, Cochrane Library, and grey literature sources, including guidelines from medical societies, were searched. The study selection process followed strict eligibility criteria, including publications in English and Portuguese focused on non-invasive treatments for LBP. The methodological quality of the studies was assessed using the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) tool. A total of 15 studies met the inclusion criteria, covering a range of non-invasive interventions such as physical therapy, exercise, acupuncture, manual therapy, and pharmacological approaches. Results: Evidence suggests that exercise-based interventions, particularly programs focused on muscle strengthening and stretching, are effective in reducing pain and improving functional outcomes in patients with mechanical LBP. Manual therapies and acupuncture also demonstrated benefits, albeit with less robust evidence. Reviewed guidelines recommend caution in the use of pharmacological interventions, such as nonsteroidal anti-inflammatory drugs (NSAIDs), particularly in chronic cases. Conclusion: This review highlights that non-invasive therapies, especially supervised exercise programs, represent the most effective and safe treatment for mechanical low back pain. The revised international guidelines reinforce the importance of avoiding early invasive interventions, except in cases of persistent or refractory pain. Appropriate management of mechanical LBP should be individualized, integrating evidence-based interventions to promote functional rehabilitation and minimize the impact of pain on patients’ quality of life.